Comparison of physicochemical and in vitro hypoglycemic activity of bamboo shoot dietary fibers from different regions of Yunnan - Dong, Yufan; Li, Qin; Guo, Yuhong; Zhao, Yihe; Cao, Jianxin (Frontiers in Nutrition, 2023)
In this study, the physicochemical properties, thermal characteristics, and in vitro hypoglycemic activity of dietary fibers extracted from four bamboo shoots were characterized and compared. The results showed that Dendrocalamus brandisii Munro (C-BSDF) had the highest dietary fiber content (6.1%) and the smallest particle size (222.21 μm). SEM observations found that C-BSDF exhibited a loose and porous microstructure, while FTIR and XRD confirmed that C-BSDF had a higher degree of decomposition of insoluble dietary fiber components and the highest crystallinity, resulting in a better microstructure. Furthermore, C-BSDF exhibited excellent physiochemical properties with the highest water hold capacity, water swelling capacity, and preferable oil holding capacity. Thermal analysis showed that C-BSDF had the lowest mass loss (64.25%) and the highest denaturation temperature (114.03°C). The hypoglycemic activity of dietary fibers from bamboo shoots were examined in vitro and followed this order of activity: C-BSDF > D-BSDF > A-BSDF > B-BSDF. The inhibition ratios of GAC, GDRI and α-amylase activity of C-BSDF were 21.57 mmol/g, 24.1%, and 23.34%, respectively. In short, C-BSDF display excellent physicochemical and functional properties due to its high soluble dietary fiber content, small particle size with a high specific surface area, and loose microstructure. Thus, Dendrocalamus brandisii Munro can be considered a promising new source of dietary fiber for hypoglycemic health products.